Measuring Student Learning in Peer Tutoring Dyads - Donahue, Annie (Qualitative and Quantitative Methods in Libraries, 2019)
The object of this study was to measure the impact of the reciprocal learning environments created in peer tutoring dyads on the peer research mentors who participated in the UNHM Research Mentor Program. The UNHM Research Mentor Program, a collaboration between the library and the college writing center, incorporates a credit-bearing tutor development course whereby all peer writing tutors receive focused information literacy instruction thereby enabling them to support student research across the entire cycle from topic selection, to information gathering (identifying need, building effective search strings, evaluating results, and incorporating information effectively), through multiple drafts to completion of the research assignment. This study utilized both qualitative and quantitative methodology to explore the impact of participation in the program from the research mentors‟ perspective. The participant sample (six women and two men) was drawn from among the students who completed the Tutor Development course between fall 2004 and spring 2013 and served at least one semester as a research mentor. The data collection methods included semi-structured interviews, a survey adapted from the Survey Regarding Satisfaction, Learning and Development of Peer Mentors in Higher Education (Posa, 2011), and document reviews of interview transcripts and Tutor Development course syllabi. Three effects of program participation were identified: 1) participants expressed uncertainty and self-doubt in their abilities to succeed initially as a research mentor; 2) participants acknowledged a perceived increase in learning and personal development; and 3) participants attributed increased learning and personal development to the reciprocal learning environment engendered in the peer-to-peer dyads. Participants in this study noted that both reciprocal environments, the peer tutoring dyads and the tutor development course cohorts, were instrumental for advancing their own learning and skill development. These collaborative learning environments supported good research practice and prepared research mentors to be effective in the one-on-one tutorial.